Language and Professional Identity - Richards, K. author. aut Link
X, 245 p.
Keywords: This book explores the ways in which professional groups develop specific interactional procedures for conducting and representing their activities, all of which contribute to a distinctive collaborative identity. It highlights the drawbacks as well as the advantages of collaborative talk, pointing to ways of improving professional performance.